PET imaging with [68Ga]-labeled TGFβ-targeting peptide in a mouse PANC-1 tumor model - Li, Yong; Zhao, Hong; Hu, Shan; Zhang, Xichen; Chen, Haojian; Zheng, Qihuang (Frontiers in Oncology, 2023)
Purpose: TGFβ is upregulated in many types of tumors and plays important roles in tumor microenvironment construction, immune escape, invasion and metastasis. Therapeutic effect of antibodies and nuclide-conjugated drugs targeting TGFβ has not been ideal. Targeting TGFβ with small-molecule or peptide carriers labeled with diagnostic/therapeutic nuclides is a new development direction. This study is aimed to explore and confirm imaging diagnostic efficiency of TGFβ-targeting peptide P144 coupled with [68Ga] in PANC-1 tumor model. Procedures: TGFβ-targeting inhibitory peptide P144 with stable activity was prepared through peptide synthesis and screening, and P144 was coupled with biological chelator DOTA and labeled with radionuclide [68Ga] to achieve a stable TGFβ-targeting tracer [68Ga]Ga-P144. This tracer was firstly used for PET molecular imaging study of pancreatic cancer in mouse PANC-1 tumor model. Results: [68Ga]Ga-P144 had a high targeted uptake and relatively long uptake retention time in tumor, and lower uptakes in non-target organs and background. Target pre-blocking experiment with the cold drug P144-DOTA demonstrated that the radioactive uptake with [68Ga]Ga-P144 PET in vivo, especially in tumor tissue, had a high TGFβ-targeting specificity. [68Ga]Ga-P144 PET had ideal imaging efficiency in PANC-1 tumor-bearing mice, with high specificity in vivo and good tumor-targeting effect. Conclusion: [68Ga]Ga-P144 has relatively high specificity and tumor-targeted uptake, and may be developed as a promising diagnostic tool for TGFβ-positive malignancies.